Spirituality and religion in older adults with dementia: a systematic review. (May 2015) - Agli, Océane; Bailly, Nathalie; Ferrand, Claude
ABSTRACT Background: Religious and spiritual issues are clearly important to the older adult population and may play a positive role in maintaining health and recovering from illness. This study systematically reviewed the literature examining the effects of religion and spirituality on health outcomes such as cognitive functioning, coping strategies, and quality of life in people with dementia. Methods: First, 51 articles with defined keywords were collected from online databases. Then, using inclusion and exclusion criteria, 11 articles were selected. These were classified according to methodological quality before being analyzed one by one. Results: The findings highlight the benefits of spirituality and religion on health outcomes. Three articles showed that in participants who used their spirituality or religion more, through their faith, their practices and in maintaining social interactions, their cognitive disorders tended to reduce or stabilize. In the other eight articles, use of spirituality or faith in daily life enabled people to develop coping strategies to help accept their disease, maintain their relationships, maintain hope, and find meaning in their lives, thereby improving their quality of life. Conclusions: Spirituality and religion appear to slow cognitive decline, and help people use coping strategies to deal their disease and have a better quality of life. This literature review allows us to take stock of research over the last decade on spirituality/religion and health outcomes. The benefits observed should be considered with caution and included in rigorous experimental research in the future.